PEMBERDAYAAN UMKM WARUNG MAKAN PANTAI DEPOK, BANTUL, YOGYAKARTA - Ida Susi Dewanti; Meilan Sugiarto; Sauptika Kancana; Eny Endah Pujiastuti; Suratna Suratna (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Depok Beach, Bantul, Yogyakarta, has a food stall center for processed seafood caught by local fishermen. The manager of a food stall at Depok Beach, Bantul, is experiencing problems in improving service quality, production efficiency, and managing small business finances. Intense competition and raw material prices force shop managers to improve service and production efficiency. The service team from the Department of Business Administration, FISIP UPN Veteran Yogyakarta collaborated with the Mina Bahari 45 Cooperative to help and assist the Depok Beach food stall in increasing business capacity. Empowerment programs that have been carried out have started from the implementation of production layouts, small business financial management, simple financial records, and improving the quality of service to consumers. Food stall managers benefit from this service program so that production times are faster, consumers are more satisfied, and finances are well recorded so that they are able to provide simple financial reports.